Small Septal Branch Artery Thrombus Inducing Ventricular Fibrillation: To Intervene or Not to Intervene. Issue 12 (February 2019) - Agarwal, Vratika; Olson, Peter C; Mroue, Jad; Olkovsky, Yefim; Bekheit, Soad; Lafferty, James
A 64-year-old woman presented for chest pain and was diagnosed with anteroseptal ST segment elevation myocardial infarction (STEMI). Emergent angiography showed 95% stenosis at the ostium of the second septal branch, consistent with thrombus, and no other significant lesions. The lesion was not amenable to intervention due to small caliber. Post angiography, the patient's electrical rhythm deteriorated into ventricular fibrillation. Following resuscitation, repeat angiography confirmed same findings. Electrophysiology study at 3 months was positive for inducing fibrillation. Due to patient risk factors, she had placement of a dual chamber defibrillator. A 5-month follow-up echocardiogram showed a small area of ventricular septal wall bowing, consistent with blood supply from septal territory.